ADVANCED LEARNING TECHNOLOGIES FOR HIGHER EDUCATION - Tsybanyuk, Oleksandra (My University, 2024)
The relevance of using modern educational technologies in higher educational institutions is increasing yearly, especially under the digitalisation and globalisation of the educational process. These technologies, including digital media communications, online platforms, and virtual and augmented reality (VR and AR), play a key role in improving students' quality of education and professional training. The study aims to assess the effectiveness of using modern educational technologies in higher educational institutions, with the object of the study being the educational processes in which these technologies are applied. The research methodology includes a literature review, questionnaires and surveys, a pedagogical experiment with control and experimental groups, and a statistical data analysis. The study's results showed that using digital media communications and online platforms significantly increases the interactivity and accessibility of educational resources, promoting active student engagement in the learning process and improving their academic achievements. Virtual and augmented reality (VR and AR) create immersive educational environments that facilitate a more profound understanding of the material and enhance student motivation. Distance learning requires the development of digital and communication skills, which is especially important in the context of the COVID-19 pandemic. The pedagogical experiment confirmed that the experimental groups of students taught using modern technologies showed better results than the control groups, who were taught using traditional methods. The practical significance of the obtained results lies in developing recommendations for the optimal use of modern educational technologies in higher educational institutions to improve the quality of education and professional training of students.
Keywords: modern educational technologies, digital media communications, online platforms, virtual reality, augmented reality, distance learning, digital skills, communication skills, higher education.